Economics of Nigeria and West Africa Population Growth: Panel ARDL Approach for West Africa - Adefemi, ADESETE Ahmed (Asian Journal of Economic Modelling, 2018)
The puzzle for the relationship between population growth and economic growth is yet to be concluded and this has generated three school of thought in this area. The first states that population growth relates positively with economic growth, the second states that population growth relates negatively with economic growth and lastly the third states that there is a neutral relationship between population growth and economic growth. This debate necessitated this study to determine the relationship between population growth and economic growth in West Africa and also Nigeria specifically. This study employs the Panel ARDL estimation technique using data which ranges from 1990-2015 for 13 West Africa countries for West Africa and the ordinary least square estimation technique for Nigeria using time series data that ranges from 1981-2015. The Pairwise Dumitrescu Hurlin Panel Causality Test and Granger causality test was also used to determine the direction of the link between population growth and economic growth. The result of the Panel ARDL regression reveals that there is a negative significant relationship between population growth and economic growth both in the short run and long run in West Africa while the OLS regression results shows that there is a positive insignificant relationship between population growth and economic growth in the short run but a negative significant relationship between population growth and economic growth in the long run in Nigeria at 10% significant level. The causality tests results indicated that there is a unidirectional causality link between economic growth and population growth and concluded that it is population growth that causes economic growth.